2022
DOI: 10.1007/s40544-022-0610-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecules with a TEMPO-based head group as high-performance organic friction modifiers

Abstract: High-performance organic friction modifiers (OFMs) added to lubricating oils are crucial for reducing energy loss and carbon footprint. To establish a new class of OFMs, we measured the friction and wear properties of N-(2,2,6,6-tetramethyl-1-oxyl-4-piperidinyl)dodecaneamide referred to as C12Amide-TEMPO. The effect of its head group chemistry, which is characterized by a rigid six-membered ring sandwiched by an amide group and a terminal free oxygen radical, was also investigated with both experiments and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 61 publications
2
15
0
Order By: Relevance
“…15,47 Throughout the simulations, a constant normal pressure of 0.5 GPa was applied by exerting a constant downward force to the atoms in the outermost layer of the upper substrate and fixing the atoms in the outermost layer of the lower substrate. Although 0.5 GPa might induce elastohydrodynamic-like behavior for PAO, 53,54 it is within the range of 0.4−1.2 GPa used in our experiments 45 and identical to that used in the previous MD study for conventional OFMs, 15 thereby facilitating comparison with the previous study. First, the Nose− Hoover thermostat 55,56 was coupled to the entire system except the fixed layer, and an equilibration run at a temperature of 393 K was executed for 0.5 ns.…”
Section: Models and Methodssupporting
confidence: 65%
See 4 more Smart Citations
“…15,47 Throughout the simulations, a constant normal pressure of 0.5 GPa was applied by exerting a constant downward force to the atoms in the outermost layer of the upper substrate and fixing the atoms in the outermost layer of the lower substrate. Although 0.5 GPa might induce elastohydrodynamic-like behavior for PAO, 53,54 it is within the range of 0.4−1.2 GPa used in our experiments 45 and identical to that used in the previous MD study for conventional OFMs, 15 thereby facilitating comparison with the previous study. First, the Nose− Hoover thermostat 55,56 was coupled to the entire system except the fixed layer, and an equilibration run at a temperature of 393 K was executed for 0.5 ns.…”
Section: Models and Methodssupporting
confidence: 65%
“…The results are shown in Figure . Because the DFT calculations suggested that O amide and O • are located at an equal distance from the surfaces for the most stable adsorbed structure of C 12 TEMPO molecules, 0.40 nm was selected as one characteristic distance for O amide , which is close to 0.38 nm for O • . The other characteristic distance was selected to be 0.50 nm because beyond this distance, both the number density and its variation are small.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations